Visum et Repertum Sebagai Alat Bukti Dalam Tindak Pidana Penganiayaan - Ni Putu Mega Cahyani; I Nyoman Sujana; Made Minggu Widiantara (Fakultas Hukum Universitas Warmadewa, 2021)
Visum et Repertum is a written statement made by doctors in forensic medicine regarding medical examinations of humans, made based on their knowledge and under oath for pro yustitia interests. As for the formulation of the problem in this case 1) how is the strength of the proof of Visum et Repertum as evidence in cases of criminal acts of abuse? 2) What effect does it have on Visum et Repertum having differences with the testimony of the defendant in a criminal act of persecution? The method in this study is a type of normative legal research, namely by conducting an assessment based on legal materials from the literature. While the problem approach used is the Legislation approach, Conceptual approach and Case approach. Visum et Repertum is a documentary evidence as stipulated in Article 184 paragraph (1) of the Criminal Procedure Code and Article 187 letter c of the Criminal Procedure Code and has a strong evidentiary power because it is able to prove the element of abuse in the case study decision No. 586/Pid.B/2018/PN Dps. The consequences arising if Visum et Repertum has a difference with the information given by the Defendant are that the information can be revoked and a re-examination of Visum et Repertum can be carried out if the Defendant is proven to give a false confession. In order for Visum et Repertum to have strong evidentiary power, it is necessary to regulate the standardization and form and arrangement of Visum et Repertum in a statutory regulation.